2002
DOI: 10.1088/0305-4470/35/33/314
|View full text |Cite
|
Sign up to set email alerts
|

A sufficient criterion for integrability of stochastic many-body dynamics and quantum spin chains

Abstract: We propose a dynamical matrix product ansatz describing the stochastic dynamics of two species of particles with excluded-volume interaction and the quantum mechanics of the associated quantum spin chains respectively. The time-dependent algebra which is obtained from the action of the Markov generator of the exclusion process (or quantum Hamiltonian of the spin chain respectively) is given in terms of a set of quadratic relations. Analyzing the permutation consistency of the induced cubic relations we obtain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…For integrable models [128,129] one may use the Bethe-ansatz and symmetry properties [18] for the explicit construction of stationary states which are not simple product measures. Using the Bethe ansatz has not been attempted yet for this class of models.…”
Section: Polymer Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For integrable models [128,129] one may use the Bethe-ansatz and symmetry properties [18] for the explicit construction of stationary states which are not simple product measures. Using the Bethe ansatz has not been attempted yet for this class of models.…”
Section: Polymer Dynamicsmentioning
confidence: 99%
“…The approach can also be extended to describe the full time evolution and hence yield time-dependent probabilities of the system evolving from some nonstationary initial distribution [131,132,133]. Popkov et al have identified the parameter manifold for which the dynamics of the 2-species ASEP can be solved using the dynamical matrix product ansatz [129]. Such models are all integrable in the sense of being associated with an integrable vertex model.…”
Section: Polymer Dynamicsmentioning
confidence: 99%
“…In this model particles of kind 1 can jump to neighboring sites if they are empty and particles of kind α = 2, 3, ..., N (called impurities) only exchange positions with others particles, satisfying a well defined dynamics. We solve this model with periodic boundary condition through a new matrix product ansatz [24,21] and we analyze the spectral gap for some special cases. Our N-ASEPI model displays the full spectrum of the ASEP [6] plus new levels.…”
Section: Resultsmentioning
confidence: 99%
“…The MPA becomes also a successful tool for the exact calculation of the stationary probability distribution of some stochastic one dimensional systems [15][16][17]. An extension of this last MPA, called dynamical MPA was introduced in [18,19] and extended in [20]. This last ansatz gives the time-dependent probability distribution for some exact integrable systems.…”
Section: Introductionmentioning
confidence: 99%